2014
DOI: 10.3168/jds.2014-8023
|View full text |Cite
|
Sign up to set email alerts
|

Modeling heat stress effect on Holstein cows under hot and dry conditions: Selection tools

Abstract: Data from milk recording of Holstein-Friesian cows together with weather information from 2 regions in Southern Spain were used to define the models that can better describe heat stress response for production traits and somatic cell score (SCS). Two sets of analyses were performed, one aimed at defining the population phenotypic response and the other at studying the genetic components. The first involved 2,514,762 test-day records from up to 5 lactations of 128,112 cows. Two models, one fitting a comfort thr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

8
79
0
2

Year Published

2016
2016
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 81 publications
(89 citation statements)
references
References 24 publications
8
79
0
2
Order By: Relevance
“…Consequently, selection for higher MY, F% or P% may result in a poor response of the poorly adapted animals to heat stress. A genetic antagonism between general production level and specific ability to respond to heat stress has also been reported in other studies on dairy cattle (Aguilar et al, 2009;Carabaño et al, 2014;Santana et al, 2016). The genetic trends show that, for MY, there was considerable genetic progress in the general production level over the years studied in all three lactations.…”
Section: Discussionmentioning
confidence: 60%
See 3 more Smart Citations
“…Consequently, selection for higher MY, F% or P% may result in a poor response of the poorly adapted animals to heat stress. A genetic antagonism between general production level and specific ability to respond to heat stress has also been reported in other studies on dairy cattle (Aguilar et al, 2009;Carabaño et al, 2014;Santana et al, 2016). The genetic trends show that, for MY, there was considerable genetic progress in the general production level over the years studied in all three lactations.…”
Section: Discussionmentioning
confidence: 60%
“…These authors reached the same conclusion in the case of severe heat stress (THI > 90). Carabaño et al (2014) reported a reduction in SCS with increasing average temperature for Spanish Holstein cows. In contrast, Brügemann et al (2012) and Hammami et al (2013) found that SCS tended to increase at both low and high THI in Holstein cows raised in the maritime region of Germany and in Luxembourg, respectively.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Indeed, Hammami et al (2013) showed that the heat stress thresholds under a continental temperate climate (Luxembourg) for production traits and somatic cell counts in Holstein cows were really lower (18°C v. values between 23°C and 30°C) than other estimates under tropical or Mediterranean climate conditions. Carabano et al (2014) showed for Holstein cows bred in Southern Spain in hot but dry conditions that their comfort thresholds could differ markedly depending on the production trait: about 29°C for milk yield, 18°C for protein yield and only 15°C for fat yield and somatic cell count. Selection criteria other than those which target production levels are now being sought in order to better evaluate the heat resistance of ruminants.…”
Section: Sparing Natural Resourcesmentioning
confidence: 99%